Hedging under hegemony: domestic pathways to autonomy in Latin America - Sims, Juan Pablo; Lee, Brice Tseen Fu (Frontiers in Political Science, 2025)
The accelerating rivalry between the United States and China has unsettled Latin America’s long-standing security hierarchy and opened limited, but tangible, space for strategic manoeuvre. This article asks why only a handful of Latin American and Caribbean governments succeed in hedging, deepening economic ties with Beijing while retaining Washington’s security umbrella, whereas ostensibly similar neighbours remain locked in one-sided alignment. Bridging hierarchy theory and new-institutional economics, it argues that effective hedging under US regional hegemony depends on a domestic triad: robust state capacity, political stability, and resilient macro-economic fundamentals. A fuzzy-set Qualitative Comparative Analysis of 14 countries (2013–2023) operationalises a novel Hedging Index that blends trade and arms-procurement shares. Six equifinal pathways emerge; all true hedgers possess at least one strong institutional or economic pillar, while states deficient in both invariably default to alignment. The findings refine hedging theory for hierarchical regions and highlight the practical value of institutional upgrading for strategic autonomy.